Controlling the reactivity of La@C82 by reduction: reaction of the La@C82 anion with alkyl halide with high regioselectivity - Maeda, Yutaka; Akita, Saeka; Suzuki, Mitsuaki; Yamada, Michio; Akasaka, Takeshi; Kobayashi, Kaoru; Nagase, Shigeru (Beilstein Journal of Organic Chemistry, 2023)
Endohedral metallofullerenes have excellent redox properties, which can be used to vary their reactivity to certain classes of molecules, such as alkyl halides. In this study, the thermal reaction of the La@C2v-C82 anion with benzyl bromide derivatives 1 at 110 °C afforded single-bonded adducts 2–5 with high regioselectivity. The products were characterized by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and visible–near infrared spectroscopy. The reaction of La@C2v-C82 with alkyl halides using the same conditions showed no consumption of La@C2v-C82, indicating that the reactivity of La@C2v-C82 toward alkyl halides was effectively increased by one-electron reduction. Single-crystal X-ray diffraction analysis of the single-bonded adduct 3a revealed the addition site of the p-methoxybenzyl group on La@C2v-C82. Theoretical calculations indicated that the addition site carbons in neutral La@C2v-C82 have high spin density, whereas those in the La@C2v-C82 anion do not have high charge densities. Thus, the reaction is believed to occur via electron transfer, followed by the radical coupling of La@C2v-C82 and benzyl radicals, rather than by bimolecular nucleophilic substitution reaction of La@C2v-C82 anion with 1.
Keywords: electron transfer; metallofullerene; radical; reduction